Approach to the first southern periphery of Granada: from the orchards to the urban villas (1920-1951) (Ciudades, 2017)
The first peripheries were supporting growth of many cities in aggregative process by which immediate spatial solutions to the new socioeconomic needs were given. Currently, these areas have gained central characteristics and need to build their historiography. The story of their past has to rebuild its bases and singularities, in order to deal with contemporary urban requirements. The article focuses on the period of genesis of “South District of Granada”, first extension to the south, as a sign of an urban history that needs to locate key moments or periods. In a process of gradual transformation from agricultural matrix, in a fragmented way and without global growth models, from the beginning this peripheral "foundation" was testing laboratory of urbanism and architecture of the time, and shows the confluence of tradition and production of new residential typological formulations.
Keywords: historiography; urban history; periphery; Granada; south; typology; urban village